Ordinal Logistic Regression for Students Academic Performance in Kurdistan Region of Iraq - Mahmood, Nozad H.; Murad, Sherko H.; Kakamad, Karwan Kakabra (Information Management and Business Review, 2018)
The First Attempt Exam is the first final exam for students after their first academic year to show their academic performance. According to the outcomes of our project, some factors influence students’ academic performance. These factors include (Sex, Car Ownership, Relationships, Smoking, Hours of Study, Facebook Use, Father Alive, Mother-Edu, and Father-Edu). These factors have a high effect on the results of the First Attempts Exam. Furthermore, females are more likely to pass the first attempts exam than the males. Also, students with cars, relationships, who smoking, use Facebook regularly, and whose mothers have higherlevels of education are negatively affected by the student’s academic performance. On the other hand, mother alive, higher level education of father, and increasing one-hour daily study are positively affected on the students’ academic performance.